Enough is enough – is it time for the Scottish Antimicrobial Prescribing Group (SAPG) to develop the third age of antimicrobial stewardship in primary care in Scotland?. Issue 2 (28th February 2020) - Malcolm, William; Baxter, Linsey; McNicol, Megan; Sneddon, Jacqueline
Abstract : Background: From 2008 the SAPG focused on 'what to prescribe' to tackle Clostridium difficile infection and from 2013 on 'whether to prescribe' to tackle unnecessary prescribing for self-limiting infections. Following these successes SAPG is now moving to the age of 'how much to prescribe' to ensure correct duration of therapy. We aimed to compare current prescribing practice with guidance from Public Health England (PHE)/NICE which recommends five days' treatment for most common community respiratory infections (RTI). Methods: The durations of antibiotic courses for treatment of respiratory tract infections was derived from data on dispensed prescriptions in 2018 from the Prescribing Information System, a national database of all NHS prescriptions dispensed in Scotland. Observed course durations were compared to course lengths recommended by PHE/NICE and modelling was undertaken on the impact on antibiotic use if durations were in line with guidance. Results: For antibiotics recommended for RTI, the most common length of treatment used was seven days. For amoxicillin the proportion of five day prescriptions varied across health boards from 1.8% to 68.7%. Modelling estimated if 75% of seven day prescriptions for antibiotics recommended for RTI were changed to five days this would deliver a 4.1% reduction in antibiotic use. Conclusion: SAPG has agreed to lead work to encourage the use of five day courses of antibiotics where indicated. Switching to five day courses would support reduction in total antibiotic use to achieve the ambitions of the UK AMR National Action Plan.